PATIENT SATISFACTION ANALYSIS BASED ON SERVICE QUALITY ASSESSMENT AND TRUST IN HEALTH FACILITIES - Agus Aan Adriansyah; Makki Makki; Budhi Setianto; Nikmatus Sa’adah; Indah Lestari; Pinky Ayu Marsela Arindis (Poltekkes Kemenkes Semarang, 2021)
Health centers have an important role to provide the best service to the community. One of the problems in the outpatient installation of the Tambelangan Health Center is the decrease in the number of patient visits. It is necessary to evaluate the quality of service so that patients put their trust and then reuse the service until they feel satisfied. The purpose of this study was to analyze the effect of service quality and trust on patient satisfaction. This research is included in the type of analytic observational using a cross-sectional approach. The sample size is 100 patients who seek treatment at the outpatient installation of the Tambelangan Health Center. The sampling technique was carried out by systematic random sampling. Data were obtained directly through the perception of the patient's assessment of the perceived service quality, their trust in the facilities and services received and including the satisfaction that the patient felt through the questionnaire instrument. The data obtained were then analyzed using binary logistic regression. The results showed that all patients (86%) stated that the overall dimensions of service quality were good, and almost all patients (81%) stated that they had believed and almost all respondents (84%) stated that they were satisfied with the service at the Outpatient Installation of the Tambelangan Health Center. Furthermore, service quality has a significant effect on patient satisfaction (p-value = 0.022) and trust has a significant effect on patient satisfaction (p-value = 0.006). The conclusion of the study shows that service quality and trust can affect patient satisfaction.